THE IMPORTANCE OF COLORITE IN TEACHING STUDENTS TO WORK ON PORTRAIT PAINTING - O’g’iloy Khudoynazarova; Botir B. Baymetov (European International Journal of Pedagogics, 2023)
The article describes the scientific theoretical and methodical foundations of portraiture in the painting type of fine art, the role of colorite in painting and its importance in teaching students to perform academic tasks. Also, the article shows the methods of teaching the rules of creating a portrait to future pedagogues